2016
DOI: 10.1002/car.2446
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Traditional and Technological Forms of Post‐Adoption Contact

Abstract: Openness in adoption practice now often includes post-adoption contact with the adopted child's birth family. Traditionally, indirect and direct contact has been supported and mediated by professionals following the adoption of children from the public care system in the UK. However, more recently, the widespread growth in the use of digital technologies has made it possible for both adopted children and birth relatives to search and contact one another through the use of sites such as Facebook without profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…She felt the desire to get some answers from her birth mother. However, as Greenhow et al (2016) found in their study of traditional and technological forms of post-adoption contact, “out of the blue” virtual contact, without prior managed contact, like the one Janette experienced, can be challenging, and she was not given any support to deal with it:Well of course you search for them. Like I’m sure everybody does it.…”
Section: Resultsmentioning
confidence: 99%
“…She felt the desire to get some answers from her birth mother. However, as Greenhow et al (2016) found in their study of traditional and technological forms of post-adoption contact, “out of the blue” virtual contact, without prior managed contact, like the one Janette experienced, can be challenging, and she was not given any support to deal with it:Well of course you search for them. Like I’m sure everybody does it.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, social media may allow others to find and view your information without your knowledge. A few studies that included the perspectives of both adoptive parents and adopted adults (primarily within the United Kingdom) found that tech-mediated contact that was used as a supplement to already established relationships with birth families helped to make contact feel less formal and thereby normalize the adoptees' dual connection with their birth family (Greenhow et al, 2016;Neil et al, 2013;Samuels, 2018).…”
Section: Tech-mediated Communication Withmentioning
confidence: 99%
“…This sentiment is echoed in the wider literature on attitudes towards young people's use of technology in which carers, adoptive parents and social workers emphasize safeguarding from online harm, risk management and the perils of overusing devices (MacDonald et al, 2017 ). Moreover, digital contact is viewed as posing significant risks to the emotional wellbeing of children and young people when it occurs ‘out‐of‐the‐blue’ or outside of an established relationship; it has been formally prohibited or is unsupported by carers and adoptive parents (Greenhow et al, 2016 ; MacDonald & McSherry, 2013 ; Neil et al, 2013 ). Yet it is important to note that a study by Sen ( 2010 ) found that even when practitioners did not have first‐hand experience of children using technology for contact, they constructed it primarily as a risk rather than an opportunity.…”
Section: Introductionmentioning
confidence: 99%